Numerical study on optimal geometric parameters of lining structures for roadway support using the artificial bee colony algorithm - Xu You-lin; Wang Min; Zhou Ze; Xu Meng-tang; Zhou Bo (Scientific Reports)
Abstract Lining structures are commonly used for roadway support in engineering practice; however, the method of determining the geometric parameters of lining structures should be properly addressed. On the one hand, the stability of roadways should be guaranteed, and on the other hand, the economy should also be considered. In this work, a numerical simulation is conducted with FLAC3D commercial software combined with the artificial bee colony algorithm, and the optimal geometric parameters of the lining structure are determined: the thickness of the bearing arc is 0.17 m, the depth of the bearing arch bottom plate reverse arch is 1.62 m. An analysis of the numerical simulation results with different lateral stress coefficients reveals that with increasing lateral stress coefficient, the thickness of the lining structure increases, and the bottom of the lining structure becomes flatter. On the basis of the numerical simulation results, the proposed method is validated and can provide a numerical basis for engineering practice.